PENGEMBANGAN LKS DISERTAI MIND MAP PADA MATERI MONERA (ARCHAEBACTERIA DAN EUBACTERIA) UNTUK SISWA KELAS X SMA - Hairani, Mega; Sudirman, Sudirman; Fitriani, Vivi (STKIP PGRI Sumbar, 2014)
ABSTRACT Study process can walk optimally, then the use of teaching materials LKS. But, LKS which is ordinary to be weared during the time still there are lacking of caused by study items which not be formulated, and existing picture black and white chromatic so that this LKS lose looks. So that, developed materials teaching LKS with Mind Map items of Monera (Archaebacteria and Eubacteria ) for the class of X high school as a mean to know and validity and the practicalities of LKS with Mind Map. This research is the development of the use of 4-D Models consisting define phase consists of a front end analysis, the analysis of the student, task analysis, concept analysis and analysis of learning objectives. Stage design media design, and then at some stage develop test the validity validator which consists of three lecturers and two teachers of SMAN 1 Dua Koto. Test practicalities by 2 teachers and 20 students of class X high school. Test results on the validity of this worksheet is 88.51% valid criteria. Test results practicalities LKS by teachers on a very practical criterion is 95.43% and the test results by the practicalities of this LKS students on criteria paktis is 85.05%, so it can be concluded that the with a Mind Map on material monera (Archaebacteria and Eubacteria) generated are valid and practical .